Justification of The Asian Literary Canon - Alfriani Ndandara (Lire Journal (Journal of Linguistics and Literature), 2017)
The term "canon" is a term in question over time because it is considered incapable of answering acertainty about the criteria used in classifying literary works. The question arose from reasons such theneglect of some literary works which containing unacceptable topics politically or have no commercialvalues in the time of its publication. Furthermore, there is a work of literature that is not recognizedbecause the author is not derived from the origin state or origin culture raised in his work. Seeing this,this research has sought to reveal the acceptable criteria in classifying literary works into a canon. Theconcept of canon used are based on Smyth, Kolbas, Lise, and Benton. Their thoughts are different butcomplete each other. The objects of this research are notable literary works from three different authorsand countries. They are Arundhati Roy, Pramoedya A. Toer, and George Orwell. Each them containdifferent issues which represented the most common issues appear in Asian countries. Throughout thethree works, the face of Asian is seen and the acceptable criteria are found. There are four criteriasuggested in this research.They are: first, the work may contain cultural and moral values of Asian ;second, the work may inform ideologies and social of the Asian; Third, it may inform the historicalvalue of Asian countries; and the last, it is already criticized and reviewed by others, in this case,researcher or readers.